King Farouk's role in establishing League of Arab States (Journal of the College of Basic Education, 2022)
The choice of the research topic came due to the importance of the establishment of the Arab League, especially after the failure of the Arab unity projects (the Fertile Crescent and Greater Syria). Egypt had a distinguished role in establishing the League of Arab States, and we discussed in this research the role of King Farouk in establishing the Arab League and his position on it.